2011
DOI: 10.1111/j.1949-8594.2011.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Preservice Teachers' Beliefs and Attitude About Teaching and Learning Mathematics Through Music: An Intervention Study

Abstract: This article presents exploratory research investigating the integration of music and a mathematics lesson as an intervention to promote preservice teachers' attitude and confidence and to extend their beliefs toward teaching mathematics integrated with music. Thirty students were randomly selected from 64 preservice teachers in a southern university. A 90‐minute mathematics lesson integrated with a music composition activity was taught by the first author. Pre‐ and postquestionnaires were provided to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…These musical concepts are related to the mathematical concepts of proportions and numerical relations, integers, logarithms and arithmetical operations and the content areas of algebra, probability, trigonometry, and geometry (Beer, 1998;Harkleroad, 2006). In the past decade, educators have implemented several different instructional strategies to provide a music-mathematics integrated curriculum, although the levels of integration have varied (An, Ma, & Capraro, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These musical concepts are related to the mathematical concepts of proportions and numerical relations, integers, logarithms and arithmetical operations and the content areas of algebra, probability, trigonometry, and geometry (Beer, 1998;Harkleroad, 2006). In the past decade, educators have implemented several different instructional strategies to provide a music-mathematics integrated curriculum, although the levels of integration have varied (An, Ma, & Capraro, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics-music integrated instruction has the potential of improving students' attitudes toward learning mathematics and of increasing students' mathematics achievement (An, Kulm, & Ma, 2008;An, Ma, & Capraro, 2011;Benes-Laffety, 1995;Omniewski, 1999). In regard to the first point, music can be used to engage students in learning mathematics in an enjoyable but also relevant way.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, design and implementation of mathematics lessons containing interdisciplinary-themed activities can provide preservice and inservice teachers with a bridge for linking mathematics pedagogy with educationally supportive resources that help make instruction meaningful and accessible for students (An, Ma, & Capraro, 2011;Cornett, 2007).…”
mentioning
confidence: 99%
“…Mathematics instruction using interdisciplinary strategies has demonstrated the capacity to support bilingual students in learning mathematics, specifically by (a) increasing students’ mathematical-themed communication during peer collaborations and working in teams (Ingram & Seashore, 2003); (b) transferring knowledge between empirical, real-life experiences and theoretical mathematical ideas (Catterall, 2005); (c) creating highly motivational mathematics learning environments encompassing decreased levels mathematics anxiety (An, Tillman, Boren, & Wang, 2014; Robertson & Lesser, 2013, 2014); and (d) improving academic achievement in mathematics as well as related cognitive skills including creativity, originality, and the ability to recognize and comprehend multiple methods of problem representation (An & Tillman, 2015; Henson, 2015). In summary, design and implementation of mathematics lessons containing interdisciplinary-themed activities can provide preservice and inservice teachers with a bridge for linking mathematics pedagogy with educationally supportive resources that help make instruction meaningful and accessible for students (An, Ma, & Capraro, 2011; Cornett, 2007).…”
mentioning
confidence: 99%
“…Our research indicated that the educational implementation of digital fabrication activities are promising, but have considerable further maturation to go before they are scalable with supports. These supports include: additional collaboration from educators interested in this development process of creating more specific lessons that are designed for their own particular content areas -for example some researchers have begun exploring the Page 23.517.12 use of educational technology to support STEM activities combining math with authentic contexts such as music; 27 provision of hardware and software for digital fabrication activities made available to schools; and peer-mentoring of teachers who are not early adopters of innovative technology by other teachers that have become early adopters of digital fabrication activities.…”
Section: Discussionmentioning
confidence: 99%